2016
DOI: 10.14687/jhs.v13i3.4120
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion as a predictor of social physique anxiety in athletes

Abstract: The purpose of this study is to examine the explanatory effect of self-compassion on social physique anxiety in athletes. The study was conducted with the participation of a total of 462 athletes, 145 female and 317 male, who were studying at Yaşar Doğu Faculty of Sport Sciences. Self-compassion Scale and Social Physique Anxiety Scale (SPAS) were used in the study. Independent sample t-test analysis showed that average scores of athletes for physical appearance comfort (PAC) t(250)=.158, p>0,5) and expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…These results were in line with a recent experimental study [ 9 ], in which higher body appreciation was associated with lower SPA. Our findings suggested also that women with a higher attitude of kindness and acceptance of perceived limits and inadequacies in relation to one’s body (i.e., body compassion) may present a lesser tendency to become worried and apprehensive about evaluating one’s physical aspects in social contexts, which is partially in line with the study by Koç and Ermis [ 10 ], who found that higher self-compassion levels were associated with lower levels of SPA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were in line with a recent experimental study [ 9 ], in which higher body appreciation was associated with lower SPA. Our findings suggested also that women with a higher attitude of kindness and acceptance of perceived limits and inadequacies in relation to one’s body (i.e., body compassion) may present a lesser tendency to become worried and apprehensive about evaluating one’s physical aspects in social contexts, which is partially in line with the study by Koç and Ermis [ 10 ], who found that higher self-compassion levels were associated with lower levels of SPA.…”
Section: Discussionsupporting
confidence: 91%
“…It was also found to predict positive body image, such as body appreciation, with which it presents a strong negative correlation [ 9 ]. Notably, high levels of self-compassion (i.e., an attitude of kindness and acceptance towards oneself) are associated with lower levels of SPA [ 10 ], which suggests that having a compassionate attitude towards one’s perceived body inadequacies (i.e., body compassion) could represent a protective factor for anxiety with respect to one’s physical appearance.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of the literature, it has been observed that several psycho-social researches have been conducted on athletes, trainers and managers interested in different branches by dealing with different variables (Riemer & Chelladurai, 1995;Summers & Russel , 1991;Maby, 1997;Garland & Barry, 1988;Gordon, 1998;Prapavessis, 1991;Doğan et al,2018;Koç and Ermiş, 2016;Kabadayı et al, 2017;Cavusoglu et al, 2017;Bostancı et al, 2017;Bayram et al, 2017;Keskin et al, 2016;Bostancı, 2014;Ermiş, 2019). Yet, psychological endurance researches on athletes are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Its feature of acceptance and kindness toward one's imperfections highlights its potential protective role in coping with the challenges posed by appearance‐related threats (Seekis et al, 2017). The negative associations between self‐compassion and self‐objectification (Daye et al, 2014; Modica, 2019; Mosewich et al, 2011), body dissatisfaction (Adams & Leary, 2007; Koç, & Ermi̇ş, E., 2016; Magnus et al, 2010; Mosewich et al, 2011; Rodgers et al, 2017), and emotional eating (Carbonneau et al, 2020) have been documented. In addition, the efficacy of self‐compassion interventions in reducing body dissatisfaction (Albertson et al, 2015), body surveillance (Toole & Craighead, 2016), and emotional eating in women (Haley et al, 2022) was proved.…”
Section: Introductionmentioning
confidence: 99%